Revolutionizing Sculpture Parks and Galleries: implementing sustainable recreational areas for engaging adventures - Ahmad Basra, Mohd Asmadzy; Ujang, Rudy; Abang, Mohammad (2024)
Across the globe, there is a growing trend of creating spaces where art, nature and sustainability come together to redefine sculpture parks and galleries. In this article, we explore the journey of McClelland’s Sculpture Park and Gallery, in Frankston, Australia and how its success could inspire a recreational attraction in Malaysia. By studying the strategies implemented by McClelland’s Sculpture Park and Gallery we can envision the potential, for developing environmentally conscious recreational areas that cater to diverse audiences in Malaysia.